Correction of the name of a recently published taxon in the Curculionini (Curculionidae) - Pelsue, Jr., Frank W.; O’brien, Charles (Zootaxa, 2012)
After publication of an article in Zootaxa (Pelsue & O’Brien, 2011), "A redefinition of the Curculionini of the world, with a key to subtribes and genera, and two new genera: Pseudoculio and Megaoculis (Coleoptera: Curculionidae: Curculioninae)", it has been brought to our attention that the generic name Megaoculis is not available as it is not a noun in the nominative singular. Megaoculis is here suppressed and Megaoculus Pelsue & O’Brien (as cited in Figure 17, page 33 in O’Brien & Pelsue, 2011) is selected as the correct alternative original spelling in compliance with Art. 11.8 and Art. 24.2.3 of the International Code of Zoological Nomenclature (ICZN, 1999).